Reconstruction of Civil Judicial Activism Limitations: A Juridical Analysis of Ultra Petita Decisions for Legal Certainty and the Principle of Party Autonomy - Nugroho, Bambang Eko (CV. Social Politic Genius (SIGn), 2025)
This research is prompted by the fundamental tension between the pursuit of substantive justice through discretionary (ex aequo et bono) decision-making and the prohibition on beyond-the-petition (ultra petita) decisions that prejudice procedural legal certainty. These dynamics have become increasingly complex following the issuance of Supreme Court Circular Number 2 of 2024. This regulation instructs judges to supplement their legal reasoning ex-officio with CTS data, which, in principle, could expand the scope of judicial activism beyond formal jurisdictional boundaries. This research aims to analyse the conceptual dialectic between judicial independence and party autonomy, to construct the boundaries of judicial activism post-implementation of Supreme Court Circular Number 2 of 2024, and to evaluate the ratio decidendi and juridical implications of land dispute decisions regarding the protection of the Defendant’s procedural rights. The research method employed is prescriptive-normative legal research, drawing on statutory, case, and conceptual approaches. The results indicate that judges’ freedom to decide cases is not absolute. This authority is constrained by the functional jurisdiction of the courts as regulated in Law Number 2 of 1986 and the imperative prohibition of Article 178 section (3) of the HIR. A paradigm comparison with Law Number 30 of 1999 reaffirms that the limitations of claims in the general judiciary must be rigidly maintained due to the compelling nature of civil procedural law (dwingend recht). The construction of judicial activism boundaries lies in the separation between strengthening the quality of legal reasoning and prohibiting unilateral additions to the material petition. Verification of the case of G. Yohana Lembang et al. proves that activism exceeding the claims results in land legal uncertainty and legitimizes an extraordinary legal remedy of Judicial Review pursuant to Article 67 point c of Law Number 14 of 1985. In conclusion, the protection of party autonomy is the primary parameter for the validity of judicial activism. The Supreme Court is advised to formulate technical guidelines for the “supplementing legal reasoning” parameter to prevent procedural law malpractice that prejudices the private rights of legal subjects.